Picornavirus and enterovirus diversity with associated human diseases - Tapparel, Caroline; Siegrist, Fredy; Petty, Tom J.; Kaiser, Laurent (Infection, genetics and evolution, 2013)
• We report recent progress regarding characterization of the natural human Picornavirus diversity. • We describe diseases associated with newly identified human picornaviruses. • We present historical perspectives on Enterovirus classification and recent breakthroughs. • We detail enterovirus and rhinovirus genetic diversity. • We highlight enterovirus phenotypic diversity. Members of the Picornaviridae family are non-enveloped, positive-stranded RNA viruses with a 30nm icosahedral capsid. This virus family exhibits a considerable amount of genetic variability driven both by mutation and recombination. Recently, three previously unknown human picornaviruses, namely the human Saffold cardiovirus, cosavirus and salivirus, have been identified in stools or respiratory samples from subjects presenting symptoms ranging from gastroenteritis to acute flaccid paralysis. However, these viruses were also frequently detected in asymptomatic subjects and their clinical relevance remains to be elucidated. The Enterovirus genus is a prototype example of the Picornaviridae heterogeneity at both genetic and phenotypic levels. This genus is divided into 10 species, seven of which contain human viruses, including three Rhinovirus species. Both human rhino- and enteroviruses are also characterized by high levels of genetic variability, as exemplified by the existence of over 250 different serotypes and the recent discovery of new enterovirus genotypes and the Rhinovirus C species. Despite their common genomic features, rhinoviruses are restricted to the respiratory tract, whereas the vast majority of enteroviruses infect the gastrointestinal tract and can spread to other organs, such as the heart or the central nervous system. Understanding the genetic determinants of such phenotypic diversity is an important challenge and a field for future investigation. Better characterization of these ubiquitous human pathogens may help to develop vaccines or antiviral treatments and to monitor the emergence of new strains.